ANALYSIS SOUNDNESS LEVEL OF FINANCIAL REPOST PT BANK PEMBAGUNAN DAERAH JAWA TIMUR TBK THE CAMELS METHODE (2019-2023 Period) - Sari, Putri Ayu Fitria; Yanti, Herlina Rahma; Nabilla, Wulan Alyu; Pratikto, Muhammad Iqbal Surya (Universitas Muhammadiyah Tangerang, 2024)
By applying the CAMEL (Capital, Asset Quality, Management, Earning and Liquidity) approach, this research seeks to determine the health condition of PT Bank Jatim Syariah Tbk in 2019 -2023. Based on the health level of PT Bank Pembangunan Daerah Jawa Timur Tbk for the period 2019 - 2023, the ROA, ROE and NI ratios are considered healthy, while the CAR, NPF, BOPO and FDR ratios are considered very healthy. Because each ratio result is in the quite healthy category, PDN is considered quite healthy.